Health implications of harmful widowhood practices in Nigeria (2011)
This article outlines an exploratory survey to determine the existence and extent of harmful widowhood practices among widows and the subsequent health implications of such practices. A detailed questionnaire was administered to 210 widows with a response of 95.24%. Findings indicated that 83.5% and 56.5% of respondents were subjected to staying indoors and wearing of black dresses respectively. Similarly, widows were commonly subjected to confiscation of husband's goods and accused of having a hand in the husband's death, with a prevalence of 20% and 18% respectively. A significant relationship also exists between these harmful widowhood practices and the respondents' health. Of the respondents, 40.5% experienced absent-mindedness, while 56% had anxiety about children's future and 13.5% already had high blood pressure. Little or no help was received from the government or non-governmental organizations. There is a need for policies from all sectors of society to help ensure widows' welfare